2019
DOI: 10.1002/cbin.11265
|View full text |Cite
|
Sign up to set email alerts
|

In Yarrowia lipolytica erythritol catabolism ends with erythrose phosphate

Abstract: In response to osmotic stress, the yeast Yarrowia lipolytica produces erythritol, a four‐carbon sugar alcohol, from erythrose‐P, an intermediate of the pentose phosphate pathway. Under non‐stressing conditions (isotonic environment), the produced erythritol is subsequently recycled into erythrose‐P that can feed the pentose phosphate pathway. Herein, gene YALI0F01584g was characterized as involved in the erythritol catabolic pathway. Several experimental evidences suggested that it encodes an erythrulose‐1P is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Although Y. lipolytica can synthesize erythritol in response to osmotic stress, it also has the ability to reconsume it in isotonic conditions. In this catabolic pathway, erythritol is first converted into erythrulose by an erythritol dehydrogenase encoded by gene EYD1 [26]. Therefore, the gene was disrupted in strains HCY109-2 (△ku70△ura3) and HCY113 (△ku70△ura3△mdh2).…”
Section: Disruption Of Yleyd1mentioning
confidence: 99%
“…Although Y. lipolytica can synthesize erythritol in response to osmotic stress, it also has the ability to reconsume it in isotonic conditions. In this catabolic pathway, erythritol is first converted into erythrulose by an erythritol dehydrogenase encoded by gene EYD1 [26]. Therefore, the gene was disrupted in strains HCY109-2 (△ku70△ura3) and HCY113 (△ku70△ura3△mdh2).…”
Section: Disruption Of Yleyd1mentioning
confidence: 99%
“…In Y. lipolytica, three genes encoding erythrose reductase have been characterized so far (namely, YALI0F18590g, YALI0D07634g and YALI0C13508g) [99,100]. We also recently elucidated the full EOL catabolic pathway [101]. It is first converted into erythrulose by an erythritol dehydrogenase (EYD1, YALI0F01650g) and subsequently phosphorylated into L-erythrulose-1P by an erythrulose kinase (EYK1, YALI0F01606g).…”
Section: Erythritolmentioning
confidence: 99%
“…It has been suggested that EUF1 (YALI0F01562g) would code for a transcription factor involved in erythritol utilization [ 28 ]. All five genes mentioned above are located in Y. lipolytica ’s chromosome F in a region called the erythritol utilization cluster [ 29 , 30 ] (Fig. 1 a), and their expression can be induced by erythritol as well as by erythrulose.…”
Section: Introductionmentioning
confidence: 99%